PENGARUH TINGKAT BUNGA DAN PENDAPATAN NASIONAL TERHADAP TABUNGAN DI INDONESIA, MALAYSIA DAN THAILAND - Lumadya Adi; Wiwik Budiarti (Jurnal Ekonomi dan Bisnis, 2015)
The purpose of the study: 1 Testing the effect of interest rates in the short term and the long-term domestic savings in Indonesia, Malaysia and Thailand. 2 Testing the influence of national income in the short term and the long-term domestic savings in Indonesia, Malaysia and Thailand. Analysis tool is a dynamic econometric model of the Partial Adjustment Model (PAM). This model applies when the independent variable is the lag of the dependent variable and must be positive and statistically significant. The results of the analysis as follows: 1. For Indonesia, short-term and long-term national income significantly influence domestic savings 2. For Indonesia, the short-term and long-term interest rate has no significant effect on domestic savings. 3. For Malaysia, the national income in the short term a significant effect on domestic savings, but can not be used long-term model. 4. For Malaysia, the short-term interest rates have a significant effect on domestic savings, but can not be used long-term model. 5. For Thailand, in the short-term and long-term national income no significant effect on domestic savings. 6. For Thailand, in the short term and long term interest rates have a significant effect on domestic savings.